China–Afghanistan Geoeconomic Cooperation and Regional Economic Integration During the Taliban Period (2021–2025) - Setiawan, Muhammad Hanif (Hasanuddin Journal of International Affairs, 2026)
China’s engagement with Afghanistan entered a new phase after the Taliban returned to power in 2021, prompting Beijing to recalibrate its westward geoeconomic strategy. This article examines how China seeks to advance regional economic integration during the Taliban period (2021–2025) through a combination of geoeconomic instruments, security–development logic, and corridor-based connectivity. Using qualitative analysis supported by secondary data, the study evaluates China’s post-2021 diplomatic initiatives, including trilateral mechanisms with Pakistan, exploratory infrastructure cooperation, and renewed interest in extending the China–Pakistan Economic Corridor (CPEC) and assessing the feasibility of the Wakhan Corridor. Findings show that the Taliban’s diplomatic shift from isolation in the 1990s to pragmatic engagement today, creates new opportunities for China’s integration agenda, particularly as the group publicly supports regional connectivity and foreign investment. However, significant structural constraints persist, including fragmented governance, militant threats, contractual instability such as the collapse of the CAPEIC oil deal, and competing regional interests. The article concludes that while China views Afghanistan as a strategic land bridge linking South and Central Asia, the realisation of corridor-based integration remains limited by Afghanistan’s institutional and security environment.